Edukasi Kebersihan Lingkungan Pesantren Al-Kholil, Jetis, Sidoarjo dengan Menerapkan Gerakan 3M (Menguras, Menutup, dan Mengubur) Guna Memberantas Jentik Nyamuk Penyebab DBD - Aziz, Ahmad Musonnifin; Kuswanto, Aris (Universitas Nahdlatul Ulama Sidoarjo, 2024)
Lack of environmental cleanliness is one of the factors that can cause the growth of mosquito larvae. Therefore, educational efforts are needed about efforts to maintain environmental cleanliness as a solution to eradicate mosquito larvae. The purpose of this education is for students to know how to maintain environmental cleanliness and efforts to prevent the growth of mosquito larvae. This education is carried out through 4 stages, namely: 1) Introduction and Pretest 2) Material Explanation 3) Posttest and 4) Mutual Cooperation with the 3M movement (Draining, Covering, and Burying). The results of the education provided showed that 86,36% of students really understood the solution to eradicating mosquito larvae